1983
DOI: 10.1111/j.1532-5415.1983.tb04872.x
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Hospitalization for Acute Illness in the Elderly

Abstract: The use of acute-care hospitals by the elderly is rising rapidly, particularly in the age group 75 and older. Any changes that will reduce the length of stay could result in considerable savings in health care costs. It is imperative to look at present policies and explore possible changes that could reduce costs by reducing the total hospital days. A study was conducted in a 290-bed county-founded community hospital in California that serves the majority of disadvantaged and poor elderly residing in an area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
2
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(73 citation statements)
references
References 10 publications
6
63
2
2
Order By: Relevance
“…This finding confirms that it is very difficult to preserve functional status during hospitalization, since many factors can influence functional status during such a time: physiopathological alterations in the elderly are worsened by acute disease, new surroundings, the absence of points of reference, being alone in the hospital ward without help from relatives, and immobility (16,22,23).…”
Section: © 2 0 0 9 E D I T R I C E K U R T I S F O R P E R S O N a supporting
confidence: 63%
See 2 more Smart Citations
“…This finding confirms that it is very difficult to preserve functional status during hospitalization, since many factors can influence functional status during such a time: physiopathological alterations in the elderly are worsened by acute disease, new surroundings, the absence of points of reference, being alone in the hospital ward without help from relatives, and immobility (16,22,23).…”
Section: © 2 0 0 9 E D I T R I C E K U R T I S F O R P E R S O N a supporting
confidence: 63%
“…Some authors (15,16) have pointed out how hospitalized elderly patients are not able to recover their lost ADL functions, but they are at even higher risk of losing independence in remaining functions, leading to higher management costs and difficulties in discharging patients to their homes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For older patients, hospitalization has been associated with a variety of adverse outcomes, including high rates of functional decline, increased risk of medical and iatrogenic events, and increased likelihood of nursing home placement upon discharge [1][2][3][4][5][6][7][8][9][10]. Low mobility, defined as activity that is limited to a bed or chair, is also a common event during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the benefi t of laparoscopic resection in terms of short-term complications and quality of life. Furthermore, studies have shown that prolonged hospital stay is independently associated with a large reduction in functional status ( 10,11 ). Th erefore, fewer complications and shorter hospital stays improve the chance of maintaining functional status, which is very important for the elderly population.…”
mentioning
confidence: 99%